TRADISI LAMARAN PEREMPUAN DALAM PERNIKAHAN ADAT JAWA PADA MASYARAKAT DESA WADENG KECAMATAN SIDAYU KABUPATEN GRESIK - Amalia, Filza; Arsana, I Wayan; Suyono, Suyono (Literasi, 2021)
The application for women in Wadeng village, Sidayu district of Gresik district is a application tradition before marriage procession performed by women to men. The tradition of application women in Javanese traditional weddings is still performed as the form of convidence of Wadeng village heritage against the heritage of the theculture of our ancestors. The purpose of this research, is to know: (1) The implementation of the marriage ceremony for women in the traditional marriage of Wadeng Village, Sidayu District, Gresik District, (2)Â Public views on the tradition of proposing women in Wadeng Village, Sidayu District, Gresik District. The form of research is qualitative research, which is data collection in a scientific setting where the researcher is the main instrument. The results of this study indicate that The implementation tradition of proposing women starts from the agreement between the family and then an application ceremony from the woman to the man is carried out to tie the two prospective brides before marriage. The public view in Wadeng village, Sidayu district of Gresik district of women application to men is not a problem if it is done or not done, according to the agreement between the two families and the tradition of proposing women is still preserved by the community of Wadeng Village, Sidayu District, Gresik District